Isoquinoline Alkaloids from Berberis vulgaris as Potential Lead Compounds for the Treatment of Alzheimer's Disease - Hostalkova, Anna; Marikova, Jana; Opletal, Lubomir; Korabecny, Jan; Hulcova, Daniela; Kunes, Jiri; Novakova, Lucie; Perez, Daniel I; Jun, Daniel; Kucera, Tomas; Andrisano, Vincenza; Siatka, Tomas; et al. (Journal of natural products, 2019)
Three new alkaloids, bersavine (3), muraricine (4), and berbostrejdine (8), together with seven known isoquinoline alkaloids (1-2, 5-7, 9, and 10) were isolated from an alkaloidal extract of the root bark of Berberis vulgaris. The structures of the isolated compounds were determined by spectroscopic methods, including 1D and 2D NMR techniques, HRMS, and optical rotation, and by comparison of the obtained data with those in the literature. The NMR data of berbamine (5), aromoline (6), and obamegine (7) were completely assigned employing 2D NMR experiments. Alkaloids isolated in sufficient amounts were evaluated for their in vitro acetylcholinesterase, butyrylcholinesterase (BuChE), prolyl oligopeptidase, and glycogen synthase kinase-3β inhibitory activities. Selected compounds were studied for their ability to permeate through the blood-brain barrier. Significant human BuChE ( hBuChE) inhibitory activity was demonstrated by 6 (IC50 = 0.82 ± 0.10 μM). The in vitro data were further supported by computational analysis that showed the accommodation of 6 in the active site of hBuChE.
Keywords: Isoquinolines; Butyrylcholinesterase; butyrylcholinesterasa; Acetylcholinesterase; Plant Exudates; rostlinné exsudáty; lidé; alkaloidy; Blood-Brain Barrier; hematoencefalická bariéra; isochinoliny; magnetická rezonanční spektroskopie; Alkaloids; acetylcholinesterasa; Alzheimer Disease; Alzheimerova nemoc; Berberis; Magnetic Resonance Spectroscopy; cholinesterasové inhibitory; Cholinesterase Inhibitors; Humans